AMIU Update for KCO 2017 - Ngatia, Dr. Peter (Amref International University, 2017)
Name: Amref International University (AMIU), the successor of Amref International Training Centre (AITC). Location: The seat of AMIU is on Langata Road, Nairobi, at the current location of Amref Health Africa HQ and the Amref International Training Centre (AITC). Vision: To be a leading university of excellence in developing transformational health leaders and practitioners. Mission: To provide holistic quality education in health sciences and related disciplines for the well-being of the society. Motto: Inspiring Lasting Change: Inìcere perpetuam mutationem
Keywords: Vision; Mission; Motto; Inspiring Lasting Change; Inìcere perpetuam mutationem; Practice-based learning; Community and public health; Academic structure; Governance; Development Plan; Library extension; Hostels; Makueni; Kenya Country Office (KCO)